Evaluation of subacute toxicity of methanolic/aqueous preparation of aerial parts of O. sanctum in Wistar rats: Clinical, haematological, biochemical and histopathological studies. (4th December 2015) - Raina, P.; Chandrasekaran, C.V.; Deepak, M.; Agarwal, A.; Ruchika, K.-G.
Abstract: Ethnopharmacological relevance: Ocimum sanctum, commonly known as Holy Basil or Tulsi has been used in Ayurveda as a demulcent, stimulant, expectorant; in the treatment of bronchitis, skin infections, malaria, diarrhoea, dysentery, arthritis, gastric and inflammatory disorders. We have previously shown that methanolic/aqueous extract of O. sanctum did not induce genotoxicity and other toxic effects in acute oral toxicity study. In the present report, we have performed sub-acute toxicity of methanolic/aqueous preparation of O. sanctum in Wistar rats to evaluate whether it induced any chronic toxic effects. Materials and methods: In subacute toxicity study, animals received O. sanctum extract (OSE) by oral gavage at the doses of 250, 500 and 1000 mg/kg/day ( n =5/group/sex) for 28 days. At the end of the study, the animals were sacrificed and evaluated for the effect of OSE on clinical, haematological, biochemical and histopathological parameters. Results: The rats treated with OSE did not show any change in body weight, food and water consumption, motor activity, sensory reactivity and foot splay measurements. There were no significant changes in haematological, pathological and biochemical parameters; and histopathology of tissues (liver, kidney, spleen, heart, and testis/ovary) among rats of either sex. OSE at a dose of 1000 mg/kg showed significant increase of Mean corpuscular hemoglobin (MCH) (19.8±0.8; 18.7±0.5) and mean corpuscular hemoglobin concentration (MCHC) (41.8±1.1; 39.3±0.7) in male and female rats in comparison to their respective controls (MCH: 17.7±0.3; 17.4±0.3; MCHC: 37.8±0.5; 36.1±0.2). Urine parameters (appearance, blood, nitrate, leucocyte, glucose, ketone, pH, protein and specific gravity) in both the male and female rats were comparable to their respective controls. In addition, no changes were observed in the vital organs of rats at macroscopic and microscopic levels. Conclusions: Our results showed that oral administration of OSE was not toxic to male and female Wistar rats upto the highest dose tested, thereby suggesting its clinical usefulness. Graphical abstract: